Efisiensi Usahatani Bibit Tebu Bagal dan Strategi Pengembangan Sistem Pembibitan di Kecamatan Balung Jember - Nur Aini Alfiah; Dewi Puspa Arisandi; Dewi Fatmawaty Sabiku (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Sugarcane is a key plantation crop and the primary source of sugar in Indonesia. However, over the past decade, rising demand has not been matched by domestic production, which has continued to decline. Improving productivity can be achieved through the use of high-quality seed. However, farmers face limited access as supply from sugar mill networks is scarce. Interest in self-producing seed remains low due to limited awareness of its comparable economic benefits to cane cultivation for milling. This study aims to assess the efficiency of seed cane production in Balung District, Jember Regency, and to identify sustainable strategies for developing an independent sugarcane seed production system at the farmer level. The results are expected to provide recommendations for farmers on improving the availability and quality of self-produced seed, serving as a reference for decision-making in developing a more efficient and sustainable sugarcane seed propagation system. The research was conducted from January to March 2025 in Balung Sub-district, Jember Regency, involving a single farmer as the primary respondent, who manages a seed production area of 1.125 hectares. Observed variables included total cost, revenue, profit, and financial efficiency parameters, such as the R/C ratio, B/C ratio, Break-Even Point (BEP), and sensitivity analysis. Data were analyzed using farm business and financial efficiency analysis methods. The results showed that bud-set sugarcane seed production is feasible and profitable, with a total cost of IDR 36,740,000.00/ha, a projected revenue of IDR 50,400,000.00/ha, and a profit of IDR 13,660,000.00 per hectare, assuming a 1:7 multiplication ratio. The R/C ratio was 1.38, and the return on investment (ROI) reached 138%. BEP and sensitivity analyses also indicated that the business remains efficient even under price fluctuations or increased production costs. It is recommended that local stakeholders support farmer training and seed certification to encourage wider adoption of independent seed production.